High-flow nasal cannula oxygen therapy as an emerging option for respiratory failure: the present and the future - Lucia Spicuzza; Matteo Schisano (SAGE Publishing, 2020)
Conventional oxygen therapy (COT) and noninvasive ventilation (NIV) have been considered for decades as frontline treatment for acute or chronic respiratory failure. However, COT can be insufficient in severe hypoxaemia whereas NIV, although highly effective, is poorly tolerated by patients and its use requires a specific expertise. High-flow nasal cannula (HFNC) is an emerging technique, designed to provide oxygen at high flows with an optimal degree of heat and humidification, which is well tolerated and easy to use in all clinical settings. Physiologically, HFNC reduces the anatomical dead space and improves carbon dioxide wash-out, reduces the work of breathing, and generates a positive end-expiratory pressure and a constant fraction of inspired oxygen. Clinically, HFNC effectively reduces dyspnoea and improves oxygenation in respiratory failure from a variety of aetiologies, thus avoiding escalation to more invasive supports. In recent years it has been adopted to treat de novo hypoxaemic respiratory failure, exacerbation of chronic obstructive pulmonary disease (COPD), postintubation hypoxaemia and used for palliative respiratory care. While the use of HFNC in acute respiratory failure is now routine as an alternative to COT and sometimes NIV, new potential applications in patients with chronic respiratory diseases (e.g. domiciliary treatment of patients with stable COPD), are currently under evaluation and will become a topic of great interest in the coming years.